The Role of The Principle of Freedom of Contract in the Implementation of International Trade Law - Muhammad Panji Mahardika; Rifqi Nur Fakhrurozi (Fakultas Hukum Universitas Djuanda, 2025)
This summary examines the crucial role of the principle of